Analisis Perbandingan Kinerja Layanan Keuangan Korporasi Di Indonesia (Studi Kasus Pada PT. Bank Mega Tbk dan PT. Bank Mega Syariah) - Ayif Fathurrahman; Harun Thalib (Universitas Islam Lamongan, 2020)
In Indonesia, the banking economy in carrying out its functions is based on the principle of prudence. The main function of banking is to collect funds from the public, and at the same time channel public funds and support the implementation of national development in order to increase the level of equitable development, national economic growth and national economic stability, towards improving the better living standards of the people. It is stated in Act Number 10 of 1998 concerning banking, that banks as business entities collect funds from the public in the form of deposits and distribute them to the public in the form of credit and or other forms in order to improve the standard of living of the community. The purpose of this research is to analize the financial performance comparison between Bank Mega (conventional) and Bank Mega Syariah from 2012 to 2018, by using these financial ratio aspects: CAR (capital adequacy ratio), NPL (non performing loan), ROA (return on assets), BOPO (biaya operasional dan pendapatan operasional), LDR (loan to deposit ratio). The data used in this research is the secondary data obtained from banking statistics issued by Otoritas Jasa Keuangan (OJK) from 2012 to 2018, with using Independent Sample T-Test analysis methode in SPSS 16 software. The result shows that there is a significant difference in LDR, NPL,BOPO ratio and no significant difference in CAR and ROA ratio between PT Bank Mega Tbk, (conventional) and PT Bank Mega Syariah In financial performance aspect, PT Bank Mega Tbk is better. However, in liquidity aspect, PT Bank Mega Syariah is better. Keywords: PT Bank Mega Tbk, PT Bank Mega Syariah, CAR, NPL, LDR, BOPO, ROA